Response of the Hydrological Cycle in Asian Monsoon Systems to Global Warming Through the Lens of Water Vapor Wave Activity Analysis. Issue 21 (4th November 2018) - Xue, Daokai; Lu, Jian; Leung, L. Ruby; Zhang, Yaocun
Abstract: The column integrated water vapor (CWV)‐based local wave activity (LWA) is adapted to examine the response of the hydrological cycle and extremes of the Asian summer monsoon in CMIP5 simulations under the RCP8.5 forcing scenario. A tight linear relationship between CWV LWA ( A + ) and its sink ( P − E + ), which measures the intensity of the local hydrological cycle and extremes, affords a simple scaling framework for the hydrological cycle intensity in terms of the contributions from (i) ratio of moisture participating in the hydrological cycle, (ii) stirring length scale, (iii) background moisture gradient, and (iv) hydrological cycling rate. Future CWV LWA over the broad Asian monsoon region shows a large increase ( 35%), attributable largely to the increase of the background moisture. The scaling analysis reveals a distinct mix of the contributing factors for the increase in ( P − E + ) between East Asian and Indian monsoon regions, despite both experiencing sizable increase of ( P − E + ) . Plain Language Summary: Budget following the material isoline can bring unique physical insight compared to the conventional budget at fixed point. This approach is applied to the output of the hydrological variables from CMIP5 simulations for both present and future climates to give a "hydrological cycle" perspective to the summer monsoonal rainfall over the Asian monsoon regions. It is found that, under the RCP8.5 warming scenario, the hydrological cycle measured by quantity ( P − E + ) is intensified over the broad Asian monsoon regions, implicative of a robust increase of the hydrological extremes there, while the hydrological cycling rate, measured by the inverse of the residence time of the integrated column moisture, shows distinct features between the Indian and Southeast Asian monsoon regions. Key Points: A contour‐following analysis is applied to water vapor to portray the hydrological cycle and its future changes over the Asian monsoon regions The resultant water vapor wave activity sink serves as a metric for hydrological extremes The hydrological cycling rate increases/decreases in the Indian/East Asian monsoons, although hydrological cycle increases in both regions